Bias Perlindungan Anak di Televisi : Tinjauan Semiotika - Nurfiana, Efen; Halwati, Umi (Universitas Islam Negeri Raden Intan Lampung, 2023)
There is a child protection bias in television shows. Television as a broadcasting medium provides entertainment, information, and the value of persuasion in changing people's ways of thinking and behavior. Television should present broadcasts in accordance with the Broadcasting Code of Conduct and Broadcasting Program Standards (P3SPS) KPI. Cases of violations committed by television are often found in advertisements, talk shows, and soap operas are no exception. As noted on Friday, March 19, 2021, KPI sent a letter of warning to subscribers of the broadcasting code of conduct. Therefore, this research needs to be done to find out the bias of child protection in television media. This research is studied using semiotics, the method used is a qualitative description. From the study conducted, this study found at least three things that contain elements of child protection bias, namely (a) violence and loss of solidarity; (b) running away from responsibilities; and (c) pregnant out of wedlock.